I am attempting to solve the following CES Utility Function problem:

CES Problem

However, I am running into issues when I get to 3).

For 1) I have $K = \left(\frac{\omega p_1}{p_2}\right)^{\frac{1}{p+1}}$

For 2) I get $X_2^M = \frac{m}{\frac{p_1}{K}+p_2} $

For 3) I find $\lambda^* = (K^\rho + \omega)^{-\frac1p-1} \cdot \omega \cdot p_2^{-1} $

and $v(p_1, p_2, m) = \left(\left(\frac{m}{p_1+Kp_2}\right)^{-\rho} + \omega(\frac{mK}{p_1+Kp_2})^{-\rho}\right)^{-1/\rho}$

I then divide $\lambda^*$ by $v(p_1, p_2, m)$, but when I do so I can't seem to fully cancel out $p_1,p_2,m,K$ and $\rho$ which I believe I would have to do to prove that they are proportional. I'm not sure if the issue is with my $\lambda^*$, my $v(p_1,p_2,m)$ or both...

Additionally, for 6) how does one demonstrate homogeneity of a given degree?


1 Answer 1


For question 3, I'm sure there are simpler solution than mine. I provide this version for your reference.

By definition, \begin{align} \lambda^* &= \frac{\frac{\partial u}{\partial x_1}(x_1^M)}{p_1} = \frac{\left[(x_1^M)^{-\rho}+ w(x_2^M)^{-\rho}\right]^{-\frac{1}{\rho}-1}(x_1^M)^{-(\rho+1)}}{p_1}\\ \\ v(p_1,p_2,m) &= u(x_1^M(p_1,p_2, m), x_2^M(p_1, p_2, m)) \\ & = \left[(x_1^M)^{-\rho}+ w(x_2^M)^{-\rho}\right]^{-\frac{1}{\rho}} \end{align} So \begin{align} \lambda^* &= v(p_1,p_2,m) \frac{1}{p_1\left[(x_1^M)^{-\rho}+ w(x_2^M)^{-\rho}\right](x_1^M)^{\rho+1}}\\ &= v(p_1,p_2,m) \frac{1}{p_1\left[x_1^M+ w\left(\frac{x_1^M}{x_2^M}\right)^{\rho+1}x_2^M\right]}\\ & = v(p_1,p_2,m) \frac{1}{p_1\left[x_1^M+ w\left(\frac{1}{\kappa}\right)^{\rho+1}x_2^M\right]} \end{align} Plug in the expression for $\kappa = \left(\frac{wp_1}{p_2}\right)^{\frac{1}{\rho+1}}$ to the equation above, we have

\begin{align} p_1\left[x_1^M+ w\left(\frac{1}{\kappa}\right)^{\rho+1}x_2^M\right] &= p_1\left[x_1^M+ w\frac{p_2}{wp_1}x_2^M\right]\\ & = p_1x_1^M + p_2x_2^M\\ & = m \end{align} so $$\lambda^* = \frac{v(p_1,p_2,m)}{m}$$

To show a function $F(x_1, x_2, ... x_n)$ is homogenous of degree $k$, simply show that $$F(kx_1, kx_2, ...kx_n) = \lambda^kF(x_1, x_2, ... x_n)$$ For $\forall \;\lambda>0$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.